Experience with a "social model" of capacity building: the Peoples-uni - Heller Richard F (BMC, 2009)
Abstract Background Taking advantage of societal trends involving the "third sector", a social model of philanthropy and the open-source software and educational resource movements, provides the opportunity for online education for capacity building at low cost. The Peoples Open Access Education Initiative, Peoples-uni, aims to help build public health capacity in this way, and this paper describes its evolution. Methods The development of the Peoples-uni has involved the creation of an administrative infrastructure, calls for and identification of volunteers, development of both the information and communications technology infrastructure and course content, and identification of students and course delivery to them. A pilot course module was offered for delivery. Results and Discussion Volunteers have been prepared to become involved in the administrative structures, as trustees, members of advisory and quality assurance and educational oversight groups. More than 100 people have offered to be involved as course developers or as facilitators for course delivery, and to date 46 of these, from 13 countries, have been actively involved. Volunteer experts in information and communications technology have extended open-source course-delivery mechanisms. Following an encouraging pilot course module, 117 students from 23 countries have enrolled in the first set of six course modules. Although the business model is not fully developed, this approach allows current module delivery at USD 50 each, to be more affordable to the target audience than traditional university-based education. Conclusion A social model of capacity building in public health has been started and has been able to attract volunteers and students from a wide range of countries. The costs are likely to be low enough to allow this method to make a substantial contribution to capacity building in low-income settings.